Dexterity of initiation and good ending In the poetry of Zuhair bin Abi Salma (Journal of the College of Basic Education, 2022)
And after praise and prayers be upon our most honorable Prophet, Abi Al-Qasim Muhammad (may God’s prayers and peace be upon him and his family and upon His companions and peace be upon him a lot).This research studies two aspects of the poem structure of the poet Zuhair bin Abi Salma Al-Muzni. They are the quick start and the good ending. The era of Zuhair bin Abi Salma is the era of the completion of the Arabic poem represented in that prelude. He mentioned the homes of the lost loved ones and standing in their traces and what they left behind around the water oases, springs and springs.The obligation to desert on a camel that has all the characteristics of strength and solidity to resist the heat of the desert